Genetic and morphometric data demonstrate alternative consequences of secondary contact in Clitarchus stick insects. (28th April 2017) - Myers, Shelley S.; Holwell, Gregory I.; Buckley, Thomas R.
Abstract: Aim: Comparisons of independent secondary contact events provide insights into allopatric speciation. The geographic distribution of Clitarchus stick insects across northern New Zealand corresponds to islands that existed in the Pliocene. Subsequent joining to the mainland provided multiple opportunities for secondary contact. We address the hypothesis that secondary contact has similar effects on parental species, across two peninsulas, due to the simultaneous removal of allopatric barriers. Location: Northland, New Zealand Methods: We explore how genetic structure relates to morphological variation and biogeographical history of Clitarchus hookeri and C. tepaki . Mitochondrial DNA sequences were used to reconstruct phylogenetical relationships. Population structure was estimated using 14 microsatellite markers. We analysed genital morphology and genetic structure within a biogeographical context to identify the consequences of independent secondary contact events. Results: Geographical patterns of genital shape indicate two independent hybrid swarms occur between C. hookeri and C. tepaki . Haplotype distributions and Bayesian cluster analyses reveal C. tepaki from the Aupouri Peninsula are distinguished from C. hookeri on the basis of both genetic structure and morphology. Clitarchus tepaki on the Karikari Peninsula did not group phylogenetically or through Bayesian clustering with C. tepaki from the Aupouri Peninsula. We observed a hybrid swarm along the Aupouri Peninsula. Main conclusions: Clitarchus species were separated on Pliocene islands and then subsequently made independent secondary contact as land connections formed. Clitarchus tepaki on the Aupouri Peninsula maintained genetic integrity; whereas we hypothesize genetic swamping has occurred on Karikari Peninsula. Our data demonstrate different outcomes of independent secondary contact events.